2021
DOI: 10.21203/rs.3.rs-409844/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrasonic Shear Device versus Monopolar Electric Cautery in Conservative Breast Surgery Following Neoadjuvant Chemotherapy: A Comparative Study

Abstract: Background: Surgical devices are commonly used during breast-conservative surgery (BCS) to provide better hemostasis. Ultrasonic shear has recently gained momentum as an effective tool for intraoperative bleeding reduction. This comparative study was designed to determine the efficacy of Harmonic focus in reducing postoperative complications of BCS following neoadjuvant chemotherapy (CTH), in comparison to the conventional method using monopolar diathermy.Methods: We conducted a prospective, non-randomized, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Regarding the length of hospital stay, which had a median value of 1 day in the two groups There was no obvious difference between the two groups in the current investigation However, compared to this current study hospital stay, some authors reported longer hospital stays (mean=4.33 days). Different management strategies and medical facilities between different centers may help to explain this [30].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the length of hospital stay, which had a median value of 1 day in the two groups There was no obvious difference between the two groups in the current investigation However, compared to this current study hospital stay, some authors reported longer hospital stays (mean=4.33 days). Different management strategies and medical facilities between different centers may help to explain this [30].…”
Section: Discussionmentioning
confidence: 99%